EVALUATION OF ANTIOXIDANT ACTIVITY OF LONG-CHAIN ESTER-FUNCTIONALIZED IMIDAZOLIUM SALTS - Startseva, Yuliia; Hodyna, Diana; Rogalskiy, Sergiy; Kovalishyn, Vasyl; Metelytsia, Larysa (Collection of scientific papers «ΛΌГOΣ», 2025)
It is known that free radicals take part in most biochemical reactions of the body, especially in oxidation processes. The earliest and non-specific violations of the body's protective and adaptive reactions under the influence of negative industrial and environmental factors are accompanied by an increase in the amount of reactive oxygen species (ROS) and, accordingly, intensification of free radical oxidation (ROР) processes [1]. Conformational changes of lipids lead to a violation of the structural and functional properties of biomembranes, an increase in their lability and permeability, an imbalance of membrane enzyme systems, and a violation of the electron transport chains of mitochondria [2].